PENGARUH TERPAAN INFORMASI PADA PROGRAM 86 DI NET TV TERHADAP KESADARAN HUKUM MASYARAKAT KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA PEKANBARU - Hafizdzoh, Nurul; Rasyid, Anuar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Mass media is a media or space that can be used to publish both information and entertainment to the public. One of the many information programs presented by the media, especially television, is the reality show program. One of them is a reality show called Net 86 which was produced in collaboration between NET and the Republic of Indonesia National Police which contains cooperation between police personnel in exposing a crime. In Cultivation theory that mass media imposes attitudes and values on the audience. The purpose of this study was to determine whether there was an effect of information exposure from the "86" program on NET TV on the legal awareness of the Simpang Tiga Village community.The method used in this research is quantitative method. Data collection tecniques in this study using a questionnaire. The number of samples for this study were 100 respondent. Sampling using simple random sampling method. To determine the influence of these two variables, the reseachers used a simple linier regresion analysis. For the processing of questinaire data, were performed using the statistical product and service solution (SPSS) Windows Version 17.Result of reseach on the effect of Indonesia Lawyers Club talkshow program against education law faculty of law, University of regretion coefficient values obtained in this study is Y=8.796 + 1.277 with a significant level of less than Î± = 0,05. This means that there are significant the effect exposure to information on the 86 in net tv program of the community law awarenes bukit raya pekanbaru city amounted to 57,3% and in the category of medium effect. These percentages shows that the Information Exposure to Programs 86 on Tv Net has an effect on the Public Legal Awareness of Simpang Tiga Village, Bukit Raya Pekanbaru City. Thus H0 is rejecte and Ha accepted.Keyword : Exposure to Information, TV Program, Society